2023
DOI: 10.1177/20533691231166543
|View full text |Cite
|
Sign up to set email alerts
|

An online survey of postmenopausal women to determine their attitudes and knowledge of the menopause

Abstract: Objective To explore postmenopausal women’s attitudes and knowledge of the menopause. Study design An online survey to evaluate women’s attitudes and knowledge of the menopause, promoted via social media. In this study, only the data from 829 women who identified as postmenopausal were analysed. Main outcome measures Quantitative and qualitative data. Results Regarding women’s attitudes towards the menopause before they went through it, 18.0% were accepting of it, 15.8% were dreading it and 5.1% were looking f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Finally, in the recent position of the North American Menopause Society, it is noted that the studies published to date can neither support nor reject the administration of isoflavone supplements or the consumption of foods containing soy. Finally, however, for the relief of mild vasomotor symptoms, he recommends the administration of isoflavones in combination with lifestyle changes as an initial treatment before the administration of drugs [44][45][46][47][48][49][50].…”
Section: Biological Impacts Of Phytoestrogensmentioning
confidence: 99%
“…Finally, in the recent position of the North American Menopause Society, it is noted that the studies published to date can neither support nor reject the administration of isoflavone supplements or the consumption of foods containing soy. Finally, however, for the relief of mild vasomotor symptoms, he recommends the administration of isoflavones in combination with lifestyle changes as an initial treatment before the administration of drugs [44][45][46][47][48][49][50].…”
Section: Biological Impacts Of Phytoestrogensmentioning
confidence: 99%
“…Furthermore, Office for National Statistic (2021) reported the median age of death for UK women is 85.8 years, which will mean a significant majority of women will live their life in the postmenopausal phase. The lack of teaching on menopause in schools and minimal education for healthcare professionals has only exacerbated this issue contributing to the lack of knowledge and its negative impact on attitudes and perceptions in women's health (Aljumah et al, 2023).…”
Section: Conte X Tmentioning
confidence: 99%
“…survey of public sector roles found similar findings with some employees responding that they might be experiencing menopausal symptoms yet reflecting how they themselves lack knowledge of their own menopause status and contributing furthermore to the poor discourse of menopause. To further highlight this issue,Aljumah et al (2023) online survey of 829 women to evaluate women's attitudes and knowledge of menopause found 94.1% of women have never been taught about menopause at school and 49.0% did not feel informed about menopause.Survey data reported employees feeling uncomfortable discussing menopause with their managers, whereas the interviews illustrated a different narrative with managers perceiving themselves to be approachable Beck et al (2020). survey found that 77% would like information on menopause provided at work; suggested that environmental factors compound individual symptoms and how they managed at work.…”
mentioning
confidence: 99%
“…10,11 Our studies have shown that peri-and postmenopausal women reported psychological symptoms more than any other. [12][13][14] What should be classed as a perimenopausal symptom is controversial, but most would agree it includes changes in menstruation which leads eventually to cessation, vasomotor symptoms such as hot flushes and night sweats, genitourinary symptoms including changes in the vagina and psychological symptoms. 13,15 Advice to women throughout their reproductive years is to balance their lifestyle with a healthy diet, exercise 16 and good quality sleep.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Our studies have shown that peri- and postmenopausal women reported psychological symptoms more than any other. 12 14 …”
Section: Introductionmentioning
confidence: 99%